Mechanisms of Ironic Meaning Formation in Literary Text (by Example of N. V. Gogol’s Novels “Evenings on a Farm near Dikanka”) - S. S. Vaulina (Tsentr nauchnykh i obrazovatelnykh proektov, 2019)
The article presents the analysis of irony as a textual category and an implicit form of expression of the author’s modality from the standpoint of cognitive linguistics. The status of the ironic assessment in the literary text is defined: its implicit character and the subjective nature is noted. The emphasis is on the deontic nature of ironic assessment: the opposition between the proper and the really existing in accordance with the generally accepted rules and values. It is emphasized that the interpretation of ironic meaning depends directly on the cognitive processes of a reader, that is, of an addressee of irony, based on the mental features of irony perception and decoding. It is noted that the main conditions for adequate decoding of irony in the literary text are the text shell of the work, which implements the author’s modality, and background knowledge of perceiving irony. The basic cognitive mechanisms of ironic meaning formation and their interrelation with intentions and critical assessment of the author in N. V. Gogol’s cycle “Evenings on a Farm near Dikanka” are established. It is concluded that the cognitive mechanisms of realization of ironic meaning are based on the conscious and purposeful violation of the author’s semantic integrity in a literary text, which is achieved in the analyzed works through a variety of cognitive techniques.